A renewable lignin-based thermoplastic adhesive for steel joining. (8th May 2023) - Kanbargi, Nihal; Hoskins, David; Gupta, Sumit; Yu, Zeyang; Shin, Yongsoon; Qiao, Yao; Merkel, Daniel R.; Bowland, Christopher C.; Labbé, Nicole; Simmons, Kevin L.; Naskar, Amit K.
Graphical abstract: Highlights: A renewable adhesive was developed from hardwood lignin biomass for joining steel substrates. Lignin content in the compositions were varied, to alter toughness, stiffness, and surface energy. Highest adhesive strength of 13.1 MPa was measured for an optimal composition. This study demonstrates the viability of lignin as a valuable building block for adhesives. Abstract: Adhesive bonding of metals has become increasingly relevant in recent years due to the demand for reducing weight and improving performance in structural applications such as automobiles and aerospace. We developed renewable thermoplastic adhesives from technical organosolv lignin isolated from hardwood biomass and acrylonitrile butadiene co-polymer rubber (NBR) for joining steel substrates. NBR33, NBR41 and NBR51 with acrylonitrile molar ratios of 33, 41 and 51%, respectively, were blended with lignin to form two-phase thermoplastic adhesives, and their adhesion, viscoelastic and surface properties were measured. Lignin content in the compositions were varied, ranging from 40% to 80% (w/w), to alter toughness, stiffness, and surface energy characteristics of the material. Better interaction or reactivity between the lignin and NBR phases was observed with greater nitrile content in NBR, leading to greater modulus and stiffness of the adhesive. Simultaneously, increasing the proportion of lignin reduced toughness and improved stiffness, with the highest adhesive strength of 13.1 MPa measured in a 60% lignin loading ratio with NBR51. Surface energy measurements revealed that total surface energy (sum of polar and dispersive surface energy) raised with lignin loading, suggesting that both surface energy and matrix strength play a critical role in the adhesive properties of the synthesized materials. A finite element-based cohesive zone model (CZM) was developed and implemented to study the failure strength of the adhesively bonded joint. This study demonstrates the viability of lignin as a valuable building block for adhesives, not only due to its inherent chemical structure and rigidity, but also for its surface energy characteristics.